(untitled) (Journal of Atomic and Molecular Sciences, 2018)
Based on the time-dependent density functional theory (TDDFT), the excited state intramolecular proton transfer (ESIPT) mechanism of a new compound 1 chromophore synthesized and designed by Liu et al. [Journal of Photochemistry and Photobiology B: Biology., 138 (2014), 75-79] has been investigated theoretically. The calculations of primary bond lengths, angles and the IR vibrational spectra verified the intramolecular hydrogen bond was strengthened. The fact that reproduced the experimental absorbance and fluorescence emission spectra well theoretically demonstrates that the TDDFT theory we adopted is reasonable and effective. In addition, intramolecular charge transfer based on the frontier molecular orbitals demonstrated the indication of the ESIPT reaction. The constructed potential energy curves of ground state and the first excited state based on keeping the O-H distance fixed at a serious of values have been used to illustrate the ESIPT process. A little barrier of 2.45 kcal/mol in the first excited state potential energy curve provided the transfer mechanism. Further, the phenomenon of fluorescence quenching has been explained reasonably based on the ESIPT mechanism.